2018
DOI: 10.1021/acs.jafc.8b01911
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Atrazine Loaded Poly (lactic-co-glycolic Acid) Nanoparticles to Ameliorate Environmental Challenges

Abstract: The use of herbicides plays a vital role in controlling weeds and conserving crops; however, its usage generates both environmental and economic problems. For example, herbicides pose a financial issue as farmers must apply large quantities to protect crops due to absorption rates of less than 0.1%. Therefore, there is a great need for the development of new methods to mitigate these issues. Here, we report for the first time the synthesis of poly(lactic- co-glycolic-acid) (PLGA) nanoherbicides loaded with atr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…For example, montmorillonite clay layers coated with a pH dependent polymer [97], core-hollow shell manganese carbonate [98], nanosized tubular halloysite and platy kaolinite [99], amino-activated iron (II,III) oxide magnetic nanoparticles [100] and nanosized rice husks [101], have been used to date. Atrazine (C) Poly (lactic-co-glycolic Acid) Potato plant - [113] In this table, the tested herbicide with the HRAC MoA group and nanocarrier are listed. Experiments conducted against targeted pests or exploring environmental factors such as off-target toxicity and soil leaching are specified.…”
Section: Nanoparticles As Carriers For Herbicidesmentioning
confidence: 99%
“…For example, montmorillonite clay layers coated with a pH dependent polymer [97], core-hollow shell manganese carbonate [98], nanosized tubular halloysite and platy kaolinite [99], amino-activated iron (II,III) oxide magnetic nanoparticles [100] and nanosized rice husks [101], have been used to date. Atrazine (C) Poly (lactic-co-glycolic Acid) Potato plant - [113] In this table, the tested herbicide with the HRAC MoA group and nanocarrier are listed. Experiments conducted against targeted pests or exploring environmental factors such as off-target toxicity and soil leaching are specified.…”
Section: Nanoparticles As Carriers For Herbicidesmentioning
confidence: 99%
“…It was observed that the root length was affected the most among these parameters. Thus, it has been proposed that PLGA nanoherbicides can be used as an alternative method to prevent weed growth [44]. Tong et al stated that nanoparticles obtained in the formulation in which metolachlor was encapsulated into mPEG-PLGA increased the solubility of hydrophobic metolachlor in water and did not contain any active substance on its surface.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, different types of nanomaterials have been used for the development of carrier systems for atrazine and other herbicides, with promising results regarding their herbicidal activity against target plants . For example, atrazine‐loaded poly(lactic‐ co ‐glycolic‐acid) nanoparticles effectively inhibited the growth of potato plants, and solid lipid nanoparticles co‐loaded with atrazine and simazine showed effective pre‐ and post‐emergence control of Raphanus raphanistrum plants . Moreover, paraquat‐containing chitosan nanoparticles had reduced toxicity to non‐target organisms in comparison with the conventional herbicide, while keeping the herbicidal activity against Brassica sp .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, different types of nanoparticles have been developed as carrier systems for atrazine, including poly(ϵ‐caprolactone), poly(lactic‐ co ‐glycolic‐acid), and solid lipid nanoparticles . Our research group have demonstrated that atrazine‐containing poly(ϵ‐caprolactone) (PCL) nanocapsules have a high encapsulation efficiency (approximately 87%) and a controlled release of the herbicide governed by relaxation of the polymer chains, in addition to being rather stable over a period of 270 days .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation